(untitled) (Perner’s Contacts, 2010)
This paper deals with a problematic of the assessment of the possibility of using of the German methodology of transport resistances for modal split changes detection of several transport means in input conditions changes. The result is a recommendation, whether that methodology usable for the purpose, even in the Czech Republic.